A Direct Writing Approach for Organic Semiconductor Single‐Crystal Patterns with Unique Orientation. Issue 17 (22nd March 2022) - Chen, Shengnan; Ma, Xiaoying; Cai, Zheren; Long, Haoran; Wang, Xiaoyu; Li, Zheng; Qu, Zhiyuan; Zhang, Fengjiao; Qiao, Yali; Song, Yanlin
Abstract: Organic semiconductor single‐crystal (OSSC) patterns with precisely controlled orientation are of great significance to the integrated fabrication of devices with high and uniform performance. However, it is still challenging to achieve purely oriented OSSC patterns due to the complex nucleation and growth process of OSSCs. Here, a general direct writing approach is presented to readily obtain high‐quality OSSC patterns with unique orientation. In specific, a direct writing method is demonstrated wherein the microscale meniscus is manipulated, which makes it possible to precisely control the nucleation and growth process of the OSSC because of its comparable size to the crystal nuclei. The resulting OSSC patterns are highly crystalline and purely oriented, in which each ribbon crystal shows a deviation angle of 33° to the printing direction. The mechanism of orientation purification is revealed experimentally and theoretically, and the results show that the TCL deformation caused by the difference in wettability and adhesive force, as well as the asymmetry of fluid concentration distribution, are the key factors leading to the selective deposition and unique orientation. Moreover, organic field‐effect transistors (OFETs) and polarization‐sensitive photodetectors are prepared based on the OSSC patterns with unique orientation, which exhibit higher device performance compared to the non‐purely oriented crystal‐based OFETs. Abstract : Achieving purely orientated single‐crystal patterns is significant but challenging for uniform and desirable performance in device integration. A direct writing approach is presented to purify the orientation through delicately manipulating the microscale meniscus. Organic field‐effect transistors (OFETs) and polarization‐sensitive photodetectors, based on the crystal patterns with unique orientation, exhibit remarkable performance, revealing great potential in organic electronics.